1997
DOI: 10.1055/s-0038-1655922
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Mobility of Integrin αIIbβ3 (Glycoprotein IIb/IIIa) in the Plasma Membrane of a Human Megakaryocyte

Abstract: SummaryThe migration of integrins to sites of cell-cell and cell-matrix contact is thought to be important for adhesion strengthening. We studied the lateral diffusion of integrin αIIbβ3 (glycoprotein Ilb/IIIa) in the plasma membrane of a cultured human megakaryocyte by fluorescence recovery after photobleaching of FITC-labelled monovalent Fab fragments directed against the P3 subunit. The diffusion of P3 on the unstimulated megakaryocyte showed a lateral diffusion coefficient (D) of 0.37 X10'9 cm2/s and a mob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
3
7
0
Order By: Relevance
“…Interference by cytochalasin D would release this constraint and shift the integrin to a conformation that is accessible to soluble fibrinogen molecules. Analysis of the mobility of α IIb β 3 by fluorescence recovery after photobleaching on a mature megakaryocyte also showed that cytochalasin D interferes with the immobilization of α IIb β 3 molecules induced by cell activation [29]. Our present data show that a similar mechanism might function in integrin α IIb β 3 binding surface‐bound fibrinogen.…”
Section: Discussionsupporting
confidence: 66%
“…Interference by cytochalasin D would release this constraint and shift the integrin to a conformation that is accessible to soluble fibrinogen molecules. Analysis of the mobility of α IIb β 3 by fluorescence recovery after photobleaching on a mature megakaryocyte also showed that cytochalasin D interferes with the immobilization of α IIb β 3 molecules induced by cell activation [29]. Our present data show that a similar mechanism might function in integrin α IIb β 3 binding surface‐bound fibrinogen.…”
Section: Discussionsupporting
confidence: 66%
“…3). These parameters for fluorescence recovery were similar to other plasma membrane proteins, including Na/K-ATPase (Paller, 1994), EGF receptor (Livneh et al, 1986), aquaporin-1 (Cho et al, 1999) and the integrin alpha IIb beta3 (Schootemeijer et al, 1997).…”
Section: Nhe3-egfp Localizes In the Juxtanuclear Region And Apical Susupporting
confidence: 65%
“…1 Given its high segmental mobility, ␣ IIb ␤ 3 should adopt a large variety of shapes also in the membrane, where its lateral and rotational mobility has been measured (19,20). The integrin model that locates the subunit N-terminal domains at the globular head and the transmembrane and cytoplasmic domains at the tail ends was based on a combination of the morphological results and secondary structure prediction (21) and confirmed by the crystallographic structure.…”
Section: Concrete Structural Features Of Integrin ␣mentioning
confidence: 96%
“…The legs of ␣ IIb ␤ 3 are flexible and emerge from the same side of the head, with their tips either separated but never reaching a diametrical disposition (the head-free tail shapes), touching (the empty oval shapes) or overlapping (the bilobular shapes) each other, or fully folded on themselves and on the head (the filled globular shapes) (18). This high degree of flexibility of the tails of the heterodimer, seen in electron micrographs and deduced from the crystallographic structure, accounts for the short rotational correlation times measured in Triton X-100 solutions by time-resolved fluorescence anisotropy.1 Given its high segmental mobility, ␣ IIb ␤ 3 should adopt a large variety of shapes also in the membrane, where its lateral and rotational mobility has been measured (19,20). The integrin model that locates the subunit N-terminal domains at the globular head and the transmembrane and cytoplasmic domains at the tail ends was based on a combination of the morphological results and secondary structure prediction (21) and confirmed by the crystallographic structure.…”
mentioning
confidence: 97%